Three dimensional SAR imaging based on vortex electromagnetic waves. Issue 4 (3rd April 2018) - Yang, Taoli; Li, Shihua; Xu, Ou; Li, Wei; Wang, Yong
ABSTRACT: A novel three dimensional (3D) synthetic aperture radar (SAR) imaging method based on vortex electromagnetic (EM) wave is proposed in this letter. Compared with the traditional two dimensional (2D) SAR imaging, the proposed method has additional resolution in azimuth angle domain by using the orbital angular momentum (OAM) carried by the vortex EM wave. Compared with the 2D radar imaging using vortex EM wave, the presented method retains the resolution in along-track direction. First, the signal model is discussed, followed by the proposed 3D imaging algorithm. For slant range and along-track directions, the traditional 2D SAR imaging methods are utilized. In order to realize azimuth angle imaging, the Doppler cell migration correction method is presented to decouple the Doppler frequency and the OAM mode. Then, the fast Fourier transformation (FFT) method can be applied to obtain the azimuth angle profile of the target. Finally, according to the imaging geometry, 3D SAR image in other coordinates can be obtained.